Optimalisasi Med-Sos Sebagai Alat Promosi Bisnis Online Bagi Ibu-Ibu Pokja Kelurahan Sukasari Tangerang - Narti Narti (Indonesian Community Service Journal of Computer Science, 2024)
The mothers of POKJA kelurahan Sukasari Tangerang are community service partners for lecturers and students of Nusa Mandiri University for the 2022-2023 even academic year of the Narti group, M.Kom. The problem that exists with service partners is the desire of POKJA mothers to develop the community's economy, by directing residents, especially housewives who have little free time, to use their time to open a side business, on the basis of this desire, POKJA mothers want to provide counseling on how to promote, but still limited knowledge they have, for this reason, POKJA mothers ask Nusa Mandiri University lecturers to carry out community service in Sukasari village, so on this basis Nusa Mandiri University Lecturers and Students want to hold community service with the title "Optimization of Med-Sos as an Online Business Promotion Tool for POKJA Mothers of Sukasari Tangerang Village". The purpose of the community service is so that POKJA mothers get new knowledge in the use of social media and later POKJA mothers will re-socialize to residents as knowledge transfer. The result of the implementation of community service activities felt by the participants of the activity was an increase in knowledge about online business promotion media.